Development of an effective cell penetrating peptide: towards viable approaches to gene delivery and chemotherapy against cancer - Covarrubias-Zambrano, Obdulia (Kansas State University, 2019)
Cancer is not only the second leading cause of death worldwide, but this disease consists of more than 200 different and unique types of cancer, making it a major challenge to develop a cancer treatment that could be effective against multiple cancer types. Multiple alternatives for cancer treatment have been exploited, and the use of therapeutic peptides (molecules capable of acting as neurotransmitters, hormones, ion channel ligands, or anti-infective/anti-cancer drugs) is among the most promising approaches. For this reason, our study focuses on developing a peptide that could be used as a nanocarrier to reach cancerous cells in a targeted manner. Here, a peptide was modified by replacing an amino acid at a specific location that would modify the peptide structure that could facilitate cellular uptake. Four peptides containing microtube-associated sequences (MTAS) and/or nuclear localization signals (NLS) were modified and synthesized following the solid phase peptide synthesis (SPPS) protocol. After cellular uptake experiments, WTAS peptide (MTAS segment containing an amino acid replaced with Trp “W”), resulted in the most effective cell penetrating peptide. Fixed and live confocal studies demonstrated that WTAS was able to penetrate cells within a couple seconds after exposure, and it was further transported to the cell nucleus in the GL26 cancerous cell within a few minutes after penetrating the cell. Interestingly enough, WTAS seemed to lose its ability to penetrate the cell nucleus when it was tested on SIM-A9, a non-cancerous cell line. More studies must be conducted to clearly demonstrate whether WTAS is capable to penetrate cell nuclei in cancer cells only. Furthermore, WTAS was used to develop a second peptide that could be an improved anti-cancer therapeutic peptide. D-SA-K6L9-AS is a highly toxic therapeutic peptide that had been previously synthesized in our research group. For our next approach, following the SPPS procedure, we synthesized a longer version of both peptides, WTAS and D-SA-K6L9-AS to create WTAS-D-SA-K6L9-AS. After successfully synthesizing this peptide, it was characterized by HPLC and MS. Cytotoxicity effects were compared to those of D-SA-K6L9-AS alone on B16F10 and GL26 cell lines, and results demonstrated that toxicity levels did not change after the addition of the WTAS peptide. Also, confocal studies determined that WTAS-D-SA-K6L9-AS still had the ability to target the mitochondria after penetration of the cell and could also reach the cell nucleus in the GL26 cell line. This behavior reflects a unique characteristic common to both peptides. Lastly, fluorescence microscope experiments determined that WTAS-D-SA-K6L9-AS kills cells in the GL26 cell line via the necrosis pathway. WTAS was further used to develop a novel gene delivery nanocarrier composed of WTAS peptide as the primary nanocarrier and poly(β-amino ester) (PBAE) polymer as the secondary nanocarrier. PBAE polymer, a nontoxic and biodegradable polymer, was used to improve the stability of WTAS peptide while facilitating the transportation into cells. After assembling and characterizing the nanocarrier, cell cytotoxicity studies were determined in three cell lines, SIM-A9, B16F10, and GL26. Finally, cell transfection was achieved by utilizing the self-assembling PBAE-WTAS nanocarrier and plasmid DNA genetically modified to express GFP (green fluorescent protein). Results demonstrated effective transfection of the GL26 cell line within 48 hours after loading the cells with the nanocarrier. This nanocarrier can be optimized by including targeting reagents in conjunction with designer plasmids against various diseases.
Keywords: Cancer; Therapeutic peptides; Nanocarrier; Confocal microscopy; Poly(β-amino ester) polymer; Transfection